Komunikasi Politik Islam Sandiaga Uno (Analisis Sistem dan Aktor di Media) - Rido Hamdani Lubis; Hasan Sazali; Icol Dianto (Ittishol: Jurnal Komunikasi dan Dakwah, 2023)
This study describes the Islamic political communication system that political actors run through the media, and this topic is interesting amidst the many views that consider politics and Islam to be separate matters that have no connection with one another. Sandiaga Uno is a political actor who is used as a researcher to see how he carries out political policies through the media. This research approach was done in a naturalistic qualitative way by looking at natural phenomena associated with Islamic political communication. This approach is carried out by looking at specific phenomena, which are then developed by looking at them in general. Islam views politics as an inseparable part of people's lives. It grows together with human civilization. Politics and Islam are inseparable; politics can bridge the spread of Islamic teachings. Good political communication will bridge the differences so that it becomes a value of brotherhood. Trustworthy actions and high obedience mark fundamental principles in Islamic politics. Mempu acts reasonably, supported by ways discussed to get results that can be jointly accounted for. Sandiaga Uno, as an object of study or an actor in the media, is used as an object of research because Sandiaga Uno has carried out many Islamic political principles to help build a more advanced Indonesia. He showed his trustworthiness, loyalty, friendship, and big heart as a political attitude that he built. This research is essential because it is inseparable from human life, and it indicates how important it is to understand how to contribute to the progress of the civilization of the Indonesian nation.